Britain, France, West Germany and the People's Republic of China, 1969-1982 The European Dimension of China's Great Transition - Albers, Martin; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book shows how the China policies of the three biggest states in Europe - Britain, France, and the Federal Republic of Germany - helped China reintegrate into the international community in the 1970s. With Europe being China's most important trading partner, the economic and political significance of Sino-European relations is obvious. Yet very little is known about the history and origins of ties between Western Europe and the People's Republic. Against the background of the Cold War, the end of Maoism, and the emergence of globalization, the governments in Bonn, Paris and London had to find ways of dealing with Europe's declining influence and promote their own national interests in Asia. Based on newly declassified government files, author Martin Albers argues that despite pursuing very different policies, these three governments supported a rapid expansion of peaceful exchange between the People's Republic and Europe and substantially contributed to the success of Beijing's reform policy.
Chapter One: Introduction -- Chapter Two: Historical Background to Sino-European Rapprochement in the 1970s -- Chapter Three: Western Europe and Détente in East Asia, 1969-1972 -- Chapter Four: Promotion of European Exports to China and the Role of Economic Diplomacy, 1969-1972 -- Chapter Five: The Diplomacy of High-Level Visits During The Twighlight of Maoism, 1973-1977 -- Chapter Six: Widening and Deepening the Relationship with China before the Reforms, 1973-1977 -- Chapter Seven: The'Alliance Era' and Strategic Cooperation with China, 1978-1982 -- Chapter Eight: Promoting Transnational Exchange with China in the Age of Reform, 1978-1982 -- Chapter Nine: Conclusion.
Keywords: Europe-History.; China-History.; World politics; International relations